Overtreatment in colorectal cancer prevention: comparison between surgical and endoscopic treatment of benign colonic polyps - Noelia Sala-Miquel; Lucía Medina-Prado; Carolina Mangas-Sanjuan; Sandra Baile-Maxía; Cristina Alenda; Lucía Madero-Velázquez; Francisco A. Ruiz-Gómez; Eva Serrano; Enrique Santana; Victor Ausina; María Sáez-Rico; Pedro Zapater; et al. (Therapeutic Advances in Gastroenterology)
Background: The growing number of premalignant colonic lesions undergoing surgical treatment can lead to increased overtreatment. Objectives: We assessed the magnitude of overtreatment by comparing rates of adverse events related to surgical and endoscopic treatment of complex benign polyps. Design: This was a single-center retrospective study conducted at a tertiary care hospital. Methods: This study included patients with benign colonic lesions treated surgically during 2005–2021 and compared with a cohort with complex lesions (Size, Morphology, Site, and Access (SMSA) ⩾3) treated endoscopically during 2018–2022. Adverse events, need for reintervention, mortality, and length of hospital stay were compared using propensity score (PS)-matching analysis. The cohorts were matched 1:1 with adjustment for sex, age, SMSA, and size as covariates. Surgical and endoscopic adverse events were described using the Clavien–Dindo (surgical group) and AGREE (endoscopic group) classifications. Results: Of 240 included patients, PS matching yielded 71 pairs. Adverse events were more frequent with surgical treatment (odds ratio (OR) 3.27; 95% confidence interval (CI) 1.59–6.71), as were severe adverse events (OR 7.5; 95% CI 2.1–27.0), need for reintervention (OR 25.6; 95% CI 3.3–200.0), and mean length of hospital stay (10 vs 0 days, p  < 0.001). One (1.4%) patient in the surgical group and none in the endoscopic group died ( p  = 0.39). Conclusion: An excess of severe adverse events with surgical treatment of complex benign polyps reflects overtreatment. Adequate pathways must be established for referral of these lesions for endoscopic treatment.